Counseling To Keep Reproductive Health Healthy With A Clean And Healthy Lifestyle Approach At Mts Al-Azhar Saumlaki - Kasmiati Arif; Arvicha Fauziah; Jakob L. Jambormias (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Reproductive health for teenagers can be realized if teenagers know correctly how to maintain their reproductive health. Teenagers need to know the basic things about a clean and healthy lifestyle. A clean and healthy lifestyle is a form of behavior carried out consciously due to learning carried out individually, by families, and in the community in realizing community health. This is an essential aspect in realizing reproductive health for teenagers. This activity aims to increase teenagers' knowledge about maintaining healthy reproductive health of teenagers using a clean and healthy lifestyle approach implemented at the AL-Azhar Saumlaki Madrasah Tsnawiyah (MTs), Tanimbar Islands Regency. The implementation method involves lectures, questions, and answers with the material presented using PowerPoint and videos displayed using an LCD. Knowledge is measured before and after the extension activities are carried out using a questionnaire. The results of community service show that there has been an increase in youth knowledge by 81%, with good knowledge. It is hoped that this counseling will provide increased knowledge to change teenagers' behavior and attitudes in maintaining their reproductive health so that they remain healthy with a clean and healthy lifestyle approach.